The Implementation of Project-Based Learning in Improving Arabic Speaking Skills: A Case Study At Ma'had Mambaus Sholihin - Husnul Fuadatun Nisa'; Zahrotul Fitri; Nurum Afi Tiyas; Salwa Azizah Zein; Uswatun Hasanah; Durrotun Nasihah; Nawa Eliyatus Shofa (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2026)
Mastering Arabic speaking skills is a primary objective of Arabic language education. However, this objective is often hindered by traditional instructional approaches that lack authentic, real-world contexts. This study aims to achieve two main objectives: (1) to explore the implementation of Project-Based Learning (PBL) in improving the Arabic speaking skills of students at Ma'had Mambaus Sholihin and (2) to identify the supporting and inhibiting factors affecting the implementation of this instructional strategy. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, classroom observations, and document analysis. The data were analyzed using the interactive analysis model, which consists of data condensation, data display, and conclusion drawing. The findings revealed two major results. First, regarding the implementation process, Project-Based Learning was carried out through three main stages: (a) establishing a supportive learning environment to foster students' self-confidence; (b) integrating authentic real-life contexts and meaningful tasks, such as market simulation activities and the production of instructional videos; and (c) implementing peer assessment and self-reflection to enhance students' metacognitive awareness. Second, concerning the influencing factors, the supporting factors included teachers' commitment and creativity, as well as students' positive responses and high levels of enthusiasm. Meanwhile, the inhibiting factors consisted of limited instructional time, inadequate learning resources, and differences in students' language proficiency levels, which required flexible group management strategies. The study concludes that Project-Based Learning is an effective instructional strategy for comprehensively improving Arabic speaking skills. These findings provide empirical evidence and practical guidance for teachers in Islamic boarding school educational settings. Furthermore, the study offers a significant theoretical contribution by enriching the academic literature through the integration of active learning and constructivist learning theories with the cultural and pedagogical characteristics of traditional Islamic educational institutions.